The Effect of Sense of Community to Brand Loyalty - Aria Bima Djoko (Universitas Trisakti, 2007)
Previous research found that loyalty programs can be distinguished by different perception in community. Furthermore, consumers are more prodigal to perceive communal programs than the use of financial incentives. Communal programs elicit stronger emotional connections and participants are significantly less predisposed to competitor switching. This research studied the effect of sense of community on resistance to competitor overtures, thus brand loyalty and brand equity among membership card user. A theoretical framework is developed to test the relationship among the study constructs. The data used in this study 100 customers, were taken as research data to test whether they are aware of the brand loyalty and brand equity or not. The results indicate that sense of community has significantinfluence on resistance to competitor overtures, and brand loyalty has a significant influence on brand equity. This study also provided partial supporl for moderating influence of sense of community.